The Impact of Teaching Sciences Through Inquiry Based Learning in a CLIL Primary Classroom - Testera Simón, Esther (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2023)
Throughout this study, the main purpose has been the observation of the impact that the inquiry-based method has had on my students’ conception about science subject. Multiple tasks and activities were implemented to engage critical thinking and problem solving. towards the end of this study, the experimental group completed a test whose results were compared with those obtained in the initial test. At the same time, a control group with similar abilities were taught based on a traditional methodology. The data was analyzed to find patterns according to these research questions: What are the main difficulties when implementing IBL to teach science through a Foreign language? can IBL change and improve students’ conception of science? can IBL develop the scientific method?